Self-confidence and Stress Coping Among Hotel Employees Handling Guests' Complaints - Retno, Desak Nyoman Arista; Sasongko, James Waskito; Oetomo, Hasan (Faculty of Psychology, Universitas Surabaya, 2010)
The purpose of this research is to find out the correlation between hotel employees’ self-confidence and stress coping when they are handling guests’ complaints. The subjects of this research are hotel employees positioned in front-office departments, housekeeping departments, and food and beverage departments of three five-star hotels in Bali. The subjects are selected according to purposive sampling technique. The data is taken from questionnaires and is analyzed by using regression analysis from Statistic Programs SPPS. According to regression analysis data process, a .719 correlation coefficient is obtained with F value of 68.644 (p < .000) which indicates significant correlation of independent variables (self-confidence) towards dependent variables (stress coping). The result of this research shows that self-confidence has correlation with employees’ stress coping when they are handling guests’ complaints. Penelitian ini dilakukan untuk mengetahui hubungan kepercayaan diri karyawan hotel terhadap stress coping ketika menangani keluhan tamu. Subyek penelitian merupakan karyawan hotel departemen front office, housekeeping, dan food and beverage dari tiga hotel bintang lima di Bali yang diambil menggunakan teknik pengambilan sampel purposive sampling. Pengambilan data dilakukan menggunakan kuesioner dan dianalisa menggunakan analisis regresi melalui program statistik SPSS. Berdasarkan pengolahan data diperoleh nilai koefisien korelasi sebesar .719 dengan F regresi sebesar 68.644 pada nilai p .000, menunjukan adanya hubungan yang signifikan dari variabel bebas (kepercayaan diri) dengan variabel tergantung (stress coping). Hasil ini menunjukkan bahwa kepercayaan diri memiliki hubungan terhadap stress coping pada karyawan hotel ketika menangani keluhan tamu.